Circular Business Models Developing a Sustainable Future - Larsson, Mats (Springer International Publishing, 2018)
This book explores the need to develop business strategies, organize and fund transformation projects and manage the transformation programme in order to further a circular economy. Circular Business Models outlines sustainable business models that can be used by companies to move transformation forward on a large scale. In addition to business models the book will cover and discuss a number of other factors necessary for a successful transformation, such as business and innovation strategy, entrepreneurship and change management. Including original interviews with circular economy practitioners, this book will be applicable to industries as diverse as manufacturing, food processing, transportation and mechanical engineering. Addressing the different challenges that meet circular economy visionaries, it outlines strategies and business models needed to gain momentum in these different sectors.